PERSEPSI PENGGUNA TERHADAP KUALITAS TAMAN SINGHA MERJOSARI BERDASARKAN VARIABEL PEMBENTUK KUALITAS RUANG PUBLIK - Praramadhanti, Gesvi Rizkitachika; Ramdlani, Subhan (Universitas Telkom, 2022)
A city with population density and all its various activities can cause mental fatigue and the deterioration of the quality of the urban living environment which results in a decrease in the productivity of urban communities. The image and quality of life of the city are often associated with open public spaces, which play a role in relaxing the pressures of life patterns and helping to reduce mental fatigue and aggresive human behavior (Praliya, 2019). City parks with good quality become one of the open public spaces that attract heterogenous urban communities, including people with disabilities. The purposive method was used in the selection of this research location. The purpose of this study was to analyze the quality of Taman Singha Merjosari which was awarded the best designed park in Indonesia in 2013. This type of research is a quantitative descriptive analysis with a sample of park users. Sari and Wicaksono (2020) evaluated the level of comfort and measurements of the microclimate in the form of temperature and humidity at Merjosari Park and Mojolangu Park. This study is different, it is based on user perceptions of the three aspects that make up the quality of public space developed by Carr (1992), namely aspect of needs, rights and meaning. The results of this study conclude that the quality of Taman Singha Merjosari is considered quite good. This reflect that several park facilities and elements need improvement, such as pedestrians, fitness equipment, children's playgrounds, and parking areas. Keywords : City, City Park, Public Space,Perception